RESEARCH OF FACTORS AFFECTING THE EFFECTIVE MANAGEMENT OF THE CITY'S HOUSING STOCK - Kakhramonov Khurshidjon Shukhrat ugli (Labor economics and human capital, 2023)
A number of significant problems have recently arisen in the activities of housing fund management organizations, including the growth of accounts receivable and accounts payable of management companies and homeowners' associations, the problem of qualified specialists in this industry is acute, as well as the failure of homeowners to fulfill their obligations to jointly manage the housing stock. This article discusses the impact of various factors on the sphere of housing management. Suggestions and recommendations are given that contribute to the sustainable development of the city's housing management system.